ASSESSMENT OF SERUM SOLUBLE UROKINASE PLASMINOGEN ACTIVATOR RECEPTOR (SUPAR) AS A POTENTIAL RISK MARKER IN OBESE WOMEN WITH PREDICTIVE MARKER FOR POLYCYSTIC OVARY SYNDROME (CAHIERS MAGELLANES-NS, 2024)
Background: Polycystic ovarian syndrome, or PCOS, is a common metabolic and endocrine disorder. It affects 5–15% of reproductive-age females. Genetic, environmental, and behavioural variables combine in the complex etiopathogenesis of PCOS.SuPAR, also called circulating uPAR, is a glycosyl-phosphatidylinositol-anchored (GPI) receptor protein with three domains (DI, DII, and DIII) that is encoded by the Plaur gene and expressed on a variety of immune cells. SuPAR has been identified as a possible predictive biomarker for a number of inflammatory illnesses due to its ability to imitate local inflammation and immune response. Objective : Assessment serum of soluble urokinase plasminogen activator receptor (suPAR) level in Iraqi PCOS patients as a potential of risk marker. Patients and Methods: One hundred eighty Iraqi women for progressing of PCOS with aged range between 20–40 years. Ninety well-diagnosed PCOS patients and ninety healthy fertile women served as the control group in an age-matched case-control study design. The groups were gathered between December 2023 and March 2024 from private laboratories and the Al-Sadr Teaching Hospital, Al-Hakeem Hospital, and Al-Zahraa Hospital in the Najaf Governorate. An enzyme-linked immunosorbant assay (ELISA) was used to test each subject's reproductive hormones (LH, FSH, TT, and TF) and suPAR level. The results were analysed with appropriate statistical methods.Results: The patient women with PCOS had significantly higher of BMI ,LH, LH/FSH ratio, TT,FAI, FIN, FSG,and, HOMA-I R women than the healthy women group. the result demonstrates that suPAR level significantly higher in PCOS patients group (P <0.0001) when compared with healthy control group. ((2.0745±0.4102)) vs(1.0442±0.3894, p˂0.0001 ) respectively. Furthermore, PCOS patients in this study had significantly higher serum suPAR levels (P = 0.0001). examine the influence of serum suPAR levels on the biochemical parameters in patients women with the PCOS is evaluated by the correlation coefficient However, Significant negative correlation were obtained between suPAR levels and IL-39 , SHBG ,FSH.While, significant positive correlation are illustrated between levels BMI,WHRM, LH, LH/FSH, TT, FIA, FSG, FIN, HOMA-IR, HOMA-%β, TG, and age with serum levels of suPAR in the patient group..suPAR had an AUC of 97.1 [95%CI (confidence interval) = 0.94-1.000, Sensitivity = %91.3, Specificity = %91.1, Cut-off point = 1.775 ng/ml].Conclusion: According to the current research, women with PCOS who have elevated levels of suPAR are also more likely to have hyperandrogenism and insulin resistance, which are risk factors for metabolic issues, endothelium and fibroblast dysfunction, and PCOS. This study addresses the connection between PCOS and SHBG, as well as related alterations in hormones and suPAR.Further research is required to fully understand the association between suPAR level and PCOS in the future.